(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What significance does the »autopoiesis« principle have in an organization? And in a society? How do we experience it in everyday space, is it »scientific emptiness« or »life fullness«? Purpose: The principle of »autopoiesis« was from the worldwide postulates placed into the scientific theory by authors in the field of organization theory and philosophy. Our aim is to check the state in local environment, regarding content and terminology, and to present the findings in a review article. The research is a part of researches inside our doctoral study in which the elements of autopoiesis in an organization are being studied. Method: Theoretical part of the research includes the overview of dimension of use and terminology in the local environment. The study comprises the triangulation of scientific literature of authors and translators. In the discussion, we will attempt to explain the content and terminological similarities, differences and dimension of use in scientific theory and practice. Results: With regard to content the authors mention two principles: »autopoiesis«, and »alopoiesis«, as a negation of first. We noted different terminology: avtopoieza/avtopoeza, alopoieza/alopoeza, their combinations suffixes. Despite the detected differences, more similarities concerning content can be observed. We offer a suggestion for the organization of the »autopoiesis« principle that is the autopoietic organization. The autopoietic principle is comprehensive in the organization theory, on the level of an individual, organization, as well as society. Organization: For the organization, it is important to explain the content of activity of the principle in the sense of autopoietic and alopoietic complex systems. The autopoietic organization is network-organized, interdisciplinary and it takes place in a circular procedure. Continuous reciprocal dynamics is characteristic, which self-renews, self-develops and is self-learning. It works autonomously and in a constant connection with the environment, as a co-dependent part that co-operates in a holistic, ethical, ecological and co-natural system. Society: Results of the incentivize an individual to achieve the autopoietic organization that leads to autopoietic society. Originality: The research contributes to the revival of the autopoietic principle activity in the scientific and social environment. Limitations/Future Research: With the original world sources, we looked into the autopoietic principle in the spheres where it has managed to establish itself in the local area so far. The research work can be continued to the establishment of autopoietic principle on all levels of the organization and society.